FLEXURAL WAVE PROPAGATION IN ANISOTROPIC FIBER COMPOSITE PLATES - Писаренко, Олександр (SWorldJournal, 2024)
Monitoring the health of structures consisting of fiber composites can be done in two ways, namely passively, by recording acoustic waves generated by cracks, impact damage, delamination and mechanical shear, and actively, by propagating diagnostic mechan